2015
DOI: 10.1007/s11515-015-1365-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in erythropoiesis and red blood cell disorders

Abstract: MicroRNAs (miRNAs) are 19-24 nucleotide non-coding ribonucleic acids binding DNA or RNA and controlling gene expression via mRNA degradation or its transcription inhibition. Erythropoies is a multi step differentiation process of erythroid progenitors to nucleate red blood cells. Maturation, proliferation and differentiation of red blood cells is affected by erythroid factors, signaling pathways in niche of hematopoietic cells, transcription factors as well as miRNAs. Expression of different types of miRNAs du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…Therefore, this molecule is a multifunctional miRNA. Increased level of miR-155 is associated with a reduction in the number of erythroid precursors, and circulating red cells (Mohammdai-asl et al, 2015;D. Zhang et al, 2017).…”
Section: The Role Of Pi3k Pathway In Autophagymentioning
confidence: 99%
“…Therefore, this molecule is a multifunctional miRNA. Increased level of miR-155 is associated with a reduction in the number of erythroid precursors, and circulating red cells (Mohammdai-asl et al, 2015;D. Zhang et al, 2017).…”
Section: The Role Of Pi3k Pathway In Autophagymentioning
confidence: 99%
“…They are also involved in other erythroid cell-associated functions, such as globin gene regulation [ 30 , 31 , 32 , 33 , 34 ], oxidant stress regulation [ 35 , 36 ], and iron absorption [ 37 ]. In a few red cell diseases, a correlation between the disease phenotype and expression levels of miRNAs has been reported [ 38 , 39 , 40 ]. Most of these studies were carried out in mouse and human erythroid cell lines and mouse primary erythroid cells.…”
Section: Introductionmentioning
confidence: 99%
“…Erythrocytes cannot synthesize miRNAs via the canonical pathway as, they are enucleated. They may retain miRNAs populations since enucleation (14). In addition, it has been observed that mature erythrocytes are proved as potential repositories of miRNAs in the circulating system (15).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can affect erythropoiesis by down regulation of miR-221, -222, -150 and -155 from transition of reticulocytes to mature erythrocytes (16,17). miR-451, -144 are reported to be upregulated during maturation of erythrocytes by GATA-1 (14,15,18). miR-451 increases the activity of FOXO3-which is involved in the control of oxidative stress and promotes synthesis of antioxidants.…”
Section: Introductionmentioning
confidence: 99%